Perancangan Interior Pusat Kreatif Cibiru Di Kota Bandung Dengan Pendekatan Berkelanjutan - Farah Fauzia, Inedita; Murdowo, Djoko; Primiana Yuniati, Arnanti (eProceedings of Art & Design, 2024)
: Bandung is one of the cities that provides many new ideas in terms of entrepreneurial creativity in Indonesia. 56% of the economy of Bandung City comes from the creative industry. In Cibiru District itself there has been an improvement in the economy after the COVID-19 pandemic. There are 6,000 MSMEs consisting of culinary (38%), services (26%), fashion (25%), and arts and crafts (11%). However, there are still many MSMEs who run their businesses individually, conventionally, and need a place to sell. There is a competition in the form of design ideas for a Cibiru creative center, discussions regarding waste processing or management issues, regional head priority programs in the form of 1 youth creativity center per region and sub-district co-working space, and the absence of facilities to be able to facilitate all the needs of the Cibiru community, especially MSMEs in one area. location, is the main reason for the need to carry out Interior Design for the Cibiru Creative Center in Bandung City with a Sustainable Approach, in order to improve the quality of the environment from an ecological, economic and social perspective. Keywords: creative center, cibiru, msmes, sustainable